Triple play as a separate market? Empirical findings and consequences to broadband market definition - Zoltán Pápai; László Lőrincz; Balázs Édes (International Telecommunications Society (ITS), 2011)
Double and triple play bundled offers are common phenomena in many national communication markets. However the overall market context, technological background of provision, the level of facility based platform competition and strategic role of the bundled offers seems to be different in national markets. There is clear challenge to the current European regulatory approach to broadband markets, which is treated as a separate market on its own. If there was a separate market for the bundled product, the whole market analysis and remedy system had to be adapted to this market reality. Testing the (triple play) bundle the market hypothesis is the logical and necessary first step to address this issue. We designed and conducted an empirical study supported by the Hungarian Competition Authority in order to address these questions. A special, situation adaptive questionnaire design was applied in order to get the possibly best informed and adequate stated preference reactions to a 10% price change. We used the cri ical loss test for market definition, testing whether there is a separate market for triple play bundles. Results indicates that the market definition question whether bundle has to or could be considered as a separate relevant market can be answered using well designed survey techniques. Many clues support the hypothesis that the triple play bundle in 2010 indeed was a separate relevant market.
Keywords: 330; triple play; double play; multi-play; bundle; market definition; SSNIP test; consumer survey; stated preference approach; critical loss